Spermidine Supplementation Protects the Liver Endothelium from Liver Damage in Mice - Genís Campreciós (MDPI AG, 2021)
Chronic liver diseases are multifactorial and the need to develop effective therapies is high. Recent studies have shown the potential of ameliorating liver disease progression through protection of the liver endothelium. Polyamine spermidine (SPD) is a caloric restriction mimetic with autophagy-enhancing properties capable of prolonging lifespan and with a proven beneficial effect in cardiovascular disease in mice and humans. We evaluated the use of dietary supplementation with SPD in two models of liver disease (CCl4 and CDAAH diet). We analyzed the effect of SPD on endothelial dysfunction in vitro and in vivo. C57BL/6J mice were supplemented with SPD in the drinking water prior and concomitantly with CCl4 and CDAAH treatments. Endothelial autophagy deficient (Atg7endo) mice were also evaluated. Liver tissue was used to evaluate the impact of SPD prophylaxis on liver damage, endothelial dysfunction, oxidative stress, mitochondrial status, inflammation and liver fibrosis. SPD improved the endothelial response to oxidative injury in vitro and improved the liver endothelial phenotype and protected against liver injury in vivo. SPD reduced the overall liver oxidative stress and improved mitochondrial fitness. The absence of benefits in the Atg7endo mice suggests an autophagy-dependent effect of SPD. This study suggests SPD diet supplementation in early phases of disease protects the liver endothelium from oxidative stress and may be an attractive approach to modify the chronic liver disease course and halt fibrosis progression.